Euclidean Relationship between the Superior Semicircular Canal and the Arcuate Eminence - Nourbakhsh, Aida; Tang, Yang; DiPace, Brian S.; Coelho, Daniel H. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Objective This study was aimed to better characterize the surgical anatomy of the floor of the middle cranial fossa using three dimensional Euclidean relationships between the arcuate eminence (AE), the superior semicircular canal (SSC), and the geniculate ganglion (GG).Study Design Submillimeter distances were recorded from computed tomography (CT) scans of 50 patients (100 sides). The AE, apex of the SSC, and the GG were identified and three dimensional distances measured.Setting The study was conducted at a tertiary academic teaching hospital.Main Outcome Measures In this study, Euclidean distance was obtained from AE to SSC by using a fixed anatomical landmark (GG) as the origin.Results On average, the AE is 2.1 ± 0.3 mm lateral, 2.5 ± 0.1 mm superior, and 2.1 ± 0.3 posterior to the SSC. Thirty percent (30/100) of patients had an AE that was less than 2 mm superior to SSC. The AE was medial to the SCC in 13% samples and anterior to the SSC in 18% samples. The results also show that there was no difference in mean distance between sides (1.08 mm; 95% confidence interval [CI] =  − 2.67–0.52; p-value = 0.29) or gender (0.56 mm; 95% CI =  − 1.34, 2.45; p-value = 0.86).Conclusions This study represents a comprehensive analysis of the relational anatomy of the floor of the middle fossa to date. In quantifying relationships between the AE, SSC, and GG, and by understanding the variability of these relationships in some planes, the middle fossa surgeon can feel more comfortable with this most challenging approach.
Keywords: middle fossa; arcuate eminence; superior semicircular canal; geniculate ganglion; anatomy